2017
DOI: 10.2134/agronj2016.11.0684
|View full text |Cite
|
Sign up to set email alerts
|

Preference, Yield, and Forage Nutritive Value of Annual Grasses under Horse Grazing

Abstract: Core Ideas Horses preferred winter wheat, annual ryegrass, and spring wheat. Annual ryegrass, spring oat, and winter barley were the highest yielding species. Spring oat, spring barley, and spring wheat had little to no regrowth. Winter wheat and winter rye consistently had higher forage nutritive values. Annual ryegrass can extend the grazing season or provide emergency forage for horses. Annual grasses such as oat (Avena sativa L.), wheat (Tricum aestivum L.), and barley (Hordeum vulgare L.) can serve as alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
9
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 47 publications
4
9
0
Order By: Relevance
“…Previous studies agree with greater CP for WW than WR [21,26,27] and a general decrease in CP over the growing period [15,25–28,32]. The CP values are consistent with previous studies performed in the Midwest region of the USA, which reported CP of 12 – 20% DM for WR [21, 26] and 11 – 34% DM for WW [22,25,26].…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Previous studies agree with greater CP for WW than WR [21,26,27] and a general decrease in CP over the growing period [15,25–28,32]. The CP values are consistent with previous studies performed in the Midwest region of the USA, which reported CP of 12 – 20% DM for WR [21, 26] and 11 – 34% DM for WW [22,25,26].…”
Section: Resultssupporting
confidence: 90%
“…Forage yield for WR was greater ( P < 0.05) than WW (Table 2), which is consistent with results of previous studies [21–24]. However, the actual yield values are inconsistent with previous studies [21–25]. Variation in yield is mainly due to factors, like year, location, and environment, which differ between studies and affect the yield of small grain forages [21,24,26,27].…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…In a pasture setting, legumes tend to be highly preferred by both sheep and cattle compared with cool‐season grasses (Boland et al, 2011, 2012; Rutter, 2006). Horses are known to be selective grazers (Allen et al, 2013; Archer, 1973a, 1973b; Hunt and Hay, 1990); yet, most research has focused on examining preference among grass pasture species (Allen et al, 2013; DeBoer et al, 2017; Grev et al, 2017). In separate experiments, horses were found to prefer Kentucky bluegrass ( Poa pratensis L.) and meadow fescue [( Festuca pratensis (Huds.)…”
mentioning
confidence: 99%